การอนุรักษณ์และการใช้ประโยชน์ความหลากหลายทางชีวภาพเพื่อพัมนาแหล่งอาหารของชุมชนในพื้นที่สะลวง อำเภอแม่แตงและอำเภอแม่ริม จังหวัดเชียงใหม่ - หาญใจ, วัชรี; พิชัย, กัลทิมา; คุณประดิษฐ์, ทัตพร; พื้นผาสุก, ณัฐธิดา; ทากัน, รุ่งนภา; บุญส่งแท้, อัครสิทธิ์; หาญเมืองใจ, ประเสริฐ (Ganesha Journal, 2012)
[บทคัดย่อภาษาไทยไม่สมบูรณ์] The study on biodiversity are conducted in the area of the Ban Eak, San Pa Yang, Mae Tang District, Chiang Mai and Phabath Seeroi, Sa Loung, Mae Rim District, Chiang Mai during March-December 2009. The aims of this study are to further promote conservation and utilization of varieties organisms such as wild mushrooms, animals and plants for the development of community as food resources. The data collected by focus group discussion, in-depth interview, questionnaire and field survey. The results were shown as followed ; The biodiversity in Phabath Seeroi was significantly higher than Ban Eak. Thirty species of wild mushrooms were found in Baan Aeak, such as Microporus. xanthopus and M. varnicipes. One hundred and forty-one species of butterfly and dragonfly were found including Gandaca harina burmana, Koruthaialos rubecula, Aristocypha fenestrella and Aethriamanta aethra. The use of plants in Ban Eak suburb was 149 species. Sixty-six species were used as medicinal plants and 83 species have been used as food such as Acmella oleracea R.K. Jansen, Diplazium esculentum Sw. and Plantago major L while Forty-four species of wild mushrooms, such as Cantharellus odoratus were found in Phabath Seeroi suburb. Resident bird and migratory bird was found of 88 and 19 species respectively, for example, Harpactes oreskios, Arachnother. magna and Clamator coromandus. Plants utilization in Phabath Seeroi suburb was 235 species. One hundred and forty-seven species were used as medicinal plants and 103 species have been used as food such as Cajanus cajan Millsp., Eurya acuminate DC. and Blumea balsamifera DC. The majority of mushrooms, birds, plants in both of areas were prepared for food in their families. However, in contrast with the medicinal plants and food plants because of the Prabath Seeroi have medicinal packaged products for traveling people in the attractive areas.